2016
DOI: 10.19030/ajbe.v9i3.9698
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Personality And Behavioral Intention In Student Teams

Abstract: This study investigated the applicability of the Big Five and FIRO-B frameworks as predictors of group process outcomes in the context of student teams.  The personality dimensions of Agreeableness, Extraversion, Conscientiousness, and Neuroticism were correlated with the interpersonal behavior dimensions of Inclusion, Affection, and Control.  The degree of association between personality and interpersonal factors differed by personality dimension.  No relationship was found for the Openness dimension.  Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…Forrester used the Bales theory in a study to look at the relationship between Personality and Behavioral Intention In Student Teams. The results are very positive where there is high in agreeableness among students to receive and invite others to be and cooperate in groups (Forrester, Tashchian, & Shore, 2016). The research proves Bales's theory of forming group cohesiveness when each member in the group has high acceptance with each other (friendly and friendly) so that they can work together in a team to achieve the goals previously set.…”
Section: Literature Reviewmentioning
confidence: 51%
“…Forrester used the Bales theory in a study to look at the relationship between Personality and Behavioral Intention In Student Teams. The results are very positive where there is high in agreeableness among students to receive and invite others to be and cooperate in groups (Forrester, Tashchian, & Shore, 2016). The research proves Bales's theory of forming group cohesiveness when each member in the group has high acceptance with each other (friendly and friendly) so that they can work together in a team to achieve the goals previously set.…”
Section: Literature Reviewmentioning
confidence: 51%
“…In the Big Five model of personality theory, agreeableness is perceived as a kind trait where individuals display friendly attitudes and behaviors toward others (Deng et al, 2017). Forrester et al (2016) indicated that students with high agreeableness actively integrate others into their activities, actively express emotions, build intimate relationships, and avoid direct control and overbearing behavior. In addition, this trait is important for identifying others’ emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Extraversion measures the interpersonal interaction of individuals toward other people in the form of being outgoing or shy, as well as the capacity for joy (Castillo, 2017). Additionally, those individuals high in extraversion are sociable, outgoing, assertive, un-reserved, and companionable; those low in extraversion tend to be quiet, reserved, and timid (McCrae and Costa, 1992;Forrester et al, 2016). Low levels of extraversion, which is introversion, showed uncomfortableness, shyness, unsociability, and reserved personality (Feist et al, 2013).…”
Section: Personality Traits and Deviant Behaviormentioning
confidence: 99%